A Comparative Study of Structural Features of Medical Bibliographic Databases: MedLib, Barakat Knowledge Network System, Irandoc, SID, Magiran and PubMed based on Gulliver Criteria - Mohsen Shirazi Mehrabad; Hadi Sharif Moghaddam; Khalil Kimiafar; Amirabbas Azizi (Tehran University of Medical Sciences, 2017)
Background and Aim: Periodic assessment of medical sciences databases is a necessary principle of the process of enhancement these databases. The aim of this study was to Comparatively evaluate structural features of medical bibliographic databases including MedLib, Barakat knowledge network system, Irandoc, SID, Magiran and  PubMed, based on Gulliver criteria. Materials and Methods: This survey was carried out in accordance with Gulliverchr('39')s assessment checklist 2002. This checklist consists of 12 sections including entry page, searching, limiting, record viewing and manipulating, graphics, record retrieval, selective dissemination of information services, general design, terminology, icon design and placement, help and advanced features. The study was conducted on five national databases and one foreign database. Results: Among the databases, PubMed gained the first ranking with a score of 89.16 percent. Among the national databases, new SID database with a score of 57.5 percent gained the top rank. Other databases including Irandoc (56.25%), Magiran (54.58 %), Barkat knowledge network system (52.91 %), MedLib (51.25%) and old SID (47.5 %) obtained next ranking respectively. Conclusion: Despite improvements indices in updated national databases, many of the indicators are far from prestigious databases such as PubMed. It is recommended that in development of national databases, features such as search, help, SDI, entry page, advanced features and record retrieval should be considered.